(untitled) (Research, Society and Development, 2022)
Sleep is vital for an individual’s rest, recovery and survival. The Intensive Care Unit (ICU) sector is highly stressful and with several factors, such as excessive sleepiness, which lead health professionals to develop a condition of stress. Burnout syndrome is defined as professional exhaustion, depersonalization and low personal fulfillment, which can happen in people who work in direct contact with other people as a result of prolonged stress. Physiotherapists are vulnerable to Burnout due to its importance in rehabilitation that requires close contact with the patient. Objective: To evaluate Burnout syndrome and its relationship with sleep in intensive care physical therapists. Method: an analytical, observational, cross-sectional study carried out in the intensive care units of a referral hospital in the city of Recife-PE, where three questionnaires were applied: Epworth Sleepiness Scale, a preliminary Burnout Identification Questionnaire (QPIB) adapted of the Maslach Burnout Inventory – MBI and a partner, demographic in 25 intensive care physical therapists. Results and discussions: There was a significant correlation between the QPIB scores and the Epworth scale (p<0.01; r= 0.47), indicating a directly proportional relationship between the variables. Conclusion: This study observed that further research is needed to raise awareness and alert professionals to the triggering factors of Burnout syndrome.